2012
DOI: 10.1016/j.biocontrol.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant phenostage and ploidy level on oviposition and feeding of two specialist herbivores of spotted knapweed, Centaurea stoebe

Abstract: h i g h l i g h t s" Agapeta zoegana oviposited significantly more on rosette and one-stem plants. " 2Â plants had significantly greater A. zoegana larval density than 4Â plants. " Significant correlation between the number of larvae infesting plant roots and Centaurea stoebe root diameter. " Cyphocleonus achates fed more frequently on multiple-stem 4Â plants. " Arion lusitanicus had a strong feeding preference for younger rosette plants. g r a p h i c a l a b s t r a c t a b s t r a c tA caged field experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Phloem‐feeding aphids were more common on diploid Gymnadenia conopsea orchids than on tetraploids, but this effect varied annually and was nonsignificant the following year (Gross and Schiestl, 2015). Using experimental arrays of diploid and tetraploid spotted knapweed, Centaurea stoebe , Collins and Müller‐Schärer (2012) showed that a root‐feeding weevil attacked tetraploids more frequently than diploids and that a generalist slug caused more damage on tetraploids, but there was no cytotype‐specific preference by a root‐feeding moth. Variation in attack has also been observed for Solidago altissima .…”
Section: Interactions With Pollinators and Floral Visitorsmentioning
confidence: 99%
“…Phloem‐feeding aphids were more common on diploid Gymnadenia conopsea orchids than on tetraploids, but this effect varied annually and was nonsignificant the following year (Gross and Schiestl, 2015). Using experimental arrays of diploid and tetraploid spotted knapweed, Centaurea stoebe , Collins and Müller‐Schärer (2012) showed that a root‐feeding weevil attacked tetraploids more frequently than diploids and that a generalist slug caused more damage on tetraploids, but there was no cytotype‐specific preference by a root‐feeding moth. Variation in attack has also been observed for Solidago altissima .…”
Section: Interactions With Pollinators and Floral Visitorsmentioning
confidence: 99%
“…It could be due either to biological controls or to generalist herbivores. Rosettes were shown to have a higher rate of damage from generalist herbivores than adult plants (Collins and Mǖller-Schärer 2012). Because herbivory rates were high in our second experiment (site 4), where the introduced biological controls were not present, it is possible that spotted knapweed seedlings may be subject to generalist herbivores in some habitats.…”
Section: Resultsmentioning
confidence: 90%
“…Spotted knapweed seedling/juvenile plant density in the sheep-grazed areas declined, in part, because fewer viable seeds were produced ( Figure 3B). Another likely contributing factor was that sheep readily consume juvenile spotted knapweed plants (Olson et al 1997), whereas Cyphocelonus, Larinus, and Agapeta primarily attack adult spotted knapweed plants (Collins and Müller-Schärer 2012;Maines et al 2013b;Smith and Story 2003). Herbivory of juvenile spotted knapweed plants by sheep is noteworthy because spotted knapweed populations often compensate in response to control treatments by increasing the rates of spotted knapweed seedling establishment or juvenile plant survival when intraspecific competition is reduced, thereby enabling spotted knapweed populations to tolerate seed loss or plant mortality (Maines et al 2013a, b;Ortega et al 2012).…”
Section: Resultsmentioning
confidence: 99%